Caries risk assessment, diagnosis and synthesis in the context of a European Core Curriculum in Cariology (2011)
This paper is part of a series outlining a European Core Curriculum in Cariology for undergraduate dental students. The European Core Curriculum in Cariology is the outcome of a process starting in 2006 and culminating in a joint workshop of the European Organization for Caries Research (ORCA) together with the Association for Dental Education in Europe (ADEE), held in Berlin from 27 to 30 June 2010. For the areas of risk assessment, diagnosis, detection, activity, monitoring and synthesis Cariology, the present paper outlines the key competencies required and the related areas in which knowledge of and familiarity with are needed for dentists graduating at the beginning of 21st century. Three major competencies were identified: Risk Assessment- competent at identifying and estimating the probability for a patient of developing new caries lesions or progression of existing lesions during a specified period of time; Diagnosis- competent through collecting, analysing and integrating data on signs and symptoms of dental caries and assess activity status of a lesion on a tooth surface to arrive at an identification of past or present occurrence of the disease caries; and Synthesis- competent at synthesising all relevant information by combining and interpreting findings from: risk assessment and diagnostic processes; from patients' needs, preferences and best interests; and from monitoring, review and re-assessment findings, when available. Similar competencies were identified for erosion and non-erosive wear. Issues that were felt by the working group panel to be important in this field are discussed, as are approaches to aid curriculum implementation.